Circular RNA ciR-02852: A novel physiological inhibitor of Porcine ovarian granulosa cell functions - Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath; Anouar Feriani; Alexander V. Sirotkin (Molecular Biology Reports, 2026)
Background Circular RNAs (circRNAs) are stable epigenetic regulators of various biological processes, yet the functional role of ciR-02852 remains unknown. This study aimed to characterize the influence of ciR-02852 on the fundamental functions of porcine ovarian granulosa cells. Methods Cells were transfected with either a ciR-02852-overexpressing vector or an shRNA ciR-02852-knockdown vector. We assessed cell viability, proliferation markers (PCNA, cyclin B1), apoptosis markers (Bax, caspase-3, and DNA fragmentation), and the secretion of steroid (progesterone, testosterone, estradiol) and peptide (IGF-I, oxytocin) hormones via RT-qPCR, immunocytochemistry, TUNEL, and ELISA. Results Overexpression of ciR-02852 significantly reduced cell viability and the expression of PCNA and cyclin B1. Conversely, it stimulated both cytoplasmic and nuclear apoptosis, as evidenced by increased Bax, caspase-3, and DNA fragmentation. Furthermore, ciR-02852 overexpression inhibited the release of all measured hormones. Silencing of ciR-02852 via shRNA yielded the opposite effects, promoting proliferation and hormone output while suppressing apoptosis. Conclusion These findings demonstrate for the first time that ciR-02852 acts as a potent physiological inhibitor of porcine ovarian cell functions. Our results indicate that ciR-02852 could be a multi-target regulator of folliculogenesis and hormone production, highlighting its potential as a diagnostic marker or therapeutic target for managing reproductive disorders and improving animal production.

Exploring the epigenetic role of the circular RNA ciR-01114 in porcine ovarian cell functions - Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath; Anouar Feriani; Alexander V. Sirotkin (Molecular Biology Reports, 2025)
Background Circular RNAs (circRNAs) are emerging epigenetic regulators in reproductive biology, but specific functions of many ovarian circRNAs remain uncharacterized. This study investigates the functional significance of circRNA ciR-01114, previously identified in porcine ovarian tissue, in modulating ovarian cell functions. Methods and results To evaluate the impact of ciR-01114 on the regulation of basic porcine ovarian granulosa cell functions, we performed experiments to increase (using an overexpressing vector) and decrease (using a shRNA vector) the expression of this circRNA. We assessed the relative expression levels of ciR-01114, cell viability, proliferation (measured by the accumulation of PCNA and cyclin B1), cytoplasmic (assessed via the accumulation of bax and caspase-3), and nuclear (DNA fragmentation) apoptosis, and the release of progesterone, testosterone, estradiol, IGF-I, and oxytocin. The overexpression of ciR-01114 significantly enhanced cell viability, proliferation, and the release of progesterone, testosterone, estradiol, and oxytocin, while suppressing apoptosis. Conversely, ciR-01114 knockdown yielded opposing effects. Conclusions These preliminary findings suggest that ciR-01114 may regulate porcine ovarian cell functions, including cell cycle progression, apoptosis, and secretory activity. However, further validation and in-depth studies are necessary to confirm these observations and fully understand the mechanisms underlying ciR-01114’s role in ovarian biology.

Brain-derived neurotrophic factor (BDNF), an autocrine/paracrine regulator of basic ovarian functions and antagonist of kisspeptin - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath; Sofía Elisa Alzuri; María Belén Montiel; Beata Fuchsová (Theriogenology, 2025)

The novel stimulators of feline ovarian granulosa cell functions: Monocyte chemoattractant protein-1 and plasminogen activator inhibitor-1 - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath (Reproductive Biology, 2024)

The microRNA miR-152 can mitigate and prevent the toxic effect of benzene on porcine ovarian cells - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Kristína Popovičová; Miroslav Bauer; Maroua Jalouli; Abdel Halim Harrath (Toxicology in Vitro, 2024)

The adipokines progranulin and omentin can directly regulate feline ovarian granulosa cell functions - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Maria Bauerová; Abdel Halim Harrath (Research in Veterinary Science, 2024)

The basic functions of rabbit ovarian granulosa cell are regulated by adipokines monocyte chemoattractant protein-1 and plasminogen activator inhibitor-1 - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath (Domestic Animal Endocrinology, 2024)

Involvement of circular RNAs in the control of porcine ovarian cell functions: Upregulation by ciR-00596 and downregulation by ciR-00646 - Zuzana Fabová; Barbora Loncová; Abdel Halim Harrath; Alexander V. Sirotkin (Reproductive Biology, 2024)

Сopper nanoparticles supported on charcoal and betacellulin – Two novel stimulators of ovarian granulosa cell functions and their functional interrelationships - Alexander V. Sirotkin; Barbora Loncová; Zuzana Fabová; Michaela Bartušová; Iris Martín-García; Abdel Halim Harrath; Francisco Alonso (Theriogenology, 2024)

Fennel affects porcine ovarian cell functions: The interrelationships with the environmental contaminant benzene - Alexander V. Sirotkin; Richard Alexa; Abdullah Alshamrani; Abdel Halim Harrath (Research in Veterinary Science, 2023)

Can flaxseed, chia or puncture vine affect mare ovarian cell functions and prevent the toxic effect of the environmental contaminant toluene? - Alexander V. Sirotkin; Adam Tarko; Zuzana Fabova; Igor Valocky; Saleh Alwasel; Jan Kotwica; Abdel Halim Harrath (Theriogenology, 2023)

Ghrelin and obestatin can promote human ovarian granulosa cell functions and FSH effects - Alexander V. Sirotkin; Adam Tarko; Miloš Mlynček; Abdel Halim Harrath (Reproductive Biology, 2023)

Ginkgo, fennel, and flaxseed can affect hormone release by porcine ovarian cells and modulate the effect of toluene - Alexander V. Sirotkin; Martina Macejková; Adam Tarko; Zuzana Fabova; Saleh Alwasel; Jan Kotwica; Abdel Halim Harrath (Reproductive Biology, 2023)

Benzene exposure causes structural and functional damage in rat ovaries: occurrence of apoptosis and autophagy - Abdel Halim Harrath; Abdulkarem Alrezaki; Maroua Jalouli; Nouf Al-Dawood; Waleed Dahmash; Lamjed Mansour; Alexander Sirotkin; Saleh Alwasel (Environmental Science and Pollution Research, 2022)

Species composition, abundance, size distribution, sex ratios, and movement of Scylla mud crabs within the mangrove ecosystem at Setiu Wetland, Terengganu, Malaysia - Hanafiah Fazhan; Mohamad N. Azra; Siti Aisah Halim; Muhamad Naimullah; Muyassar H. Abualreesh; Alexander Chong Shu-Chien; Youji Wang; Yushinta Fujaya; Mohammad Syahnon; Hongyu Ma; Khor Waiho; Mhd Ikhwanuddin (Frontiers in Marine Science, 2022)
The aim of the present study was to determine the movement patterns of mud crabs, genus Scylla , within the mangrove area of the Setiu Wetland in Terengganu, Malaysia. Mark-release-recapture technique were conducted during 24 sampling trips. A fluorescent visible implant elastomer (VIE) tag was inserted within the crab’s shell and they were released at the same capture stations over an interval of two weeks before the next sampling. A total of 288 crabs of various sizes, sex and species were identified, measured, tagged and recorded. The numbers of male crabs were higher than females. Three species were present, dominated by S. olivacea at 54.2% and S.tranquebarica at 26.4%, with S. paramamosain in third place at 19.4%. Among the 288 crabs that were tagged and released, 26.38% were recaptured. The tagged crabs did not move very far from the release station based on the recapture data. The greatest mean chance of being recaptured within 24 h was 44.5%, and there were no tagged crabs recaptured after 48 h even on sampling trips at several points from the release site. Knowledge of movement patterns is essential to understand migration and population dynamics and the relationship between reproduction and local distribution.

Buckwheat, rooibos, and vitex extracts can mitigate adverse effects of xylene on ovarian cells in vitro - Alexander V. Sirotkin; Martina Macejková; Adam Tarko; Zuzana Fabova; Saleh Alwasel; Abdel Halim Harrath (Environmental Science and Pollution Research, 2021)

Effects of benzene on gilts ovarian cell functions alone and in combination with buckwheat, rooibos, and vitex - Alexander V. Sirotkin; Martina Macejková; Adam Tarko; Zuzana Fabova; Abdulkarem Alrezaki; Saleh Alwasel; Abdel Halim Harrath (Environmental Science and Pollution Research, 2021)

Recent Progress in Engineering Mesenchymal Stem Cell Differentiation - Alexander Halim; Agnes Dwi Ariyanti; Qing Luo; Guanbin Song (Stem Cell Reviews and Reports, 2020)

Plant isoflavones can prevent adverse effects of benzene on porcine ovarian activity: an in vitro study - Alexander Sirotkin; Zuzana Záhoranska; Adam Tarko; Florina Popovska-Percinic; Saleh Alwasel; Abdel Halim Harrath (Environmental Science and Pollution Research, 2020)

Mechanisms of the direct effects of oil-related contaminants on ovarian cells - Alexander V. Sirotkin; Attila Kadasi; Andrej Baláži; Jan Kotwica; Abdulkarem Alrezaki; Abdel Halim Harrath (Environmental Science and Pollution Research, 2020)

MicroRNAs control transcription factor NF-kB (p65) expression in human ovarian cells - Alexander V. Sirotkin; Richard Alexa; Gabriela Kišová; Abdel Halim Harrath; Saleh Alwasel; Dmitriy Ovcharenko; Miloš Mlynček (Functional & Integrative Genomics, 2015)

Infertility in the hyperplasic ovary of freshwater planarians: the role of programmed cell death - Abdel Halim Harrath; Abdelhabib Semlali; Lamjed Mansour; Mukhtar Ahmed; Alexander V. Sirotkin; Suliman Y. Al Omar; Maha Arfah; Mohamed S. Al Anazi; Ibrahim M. Alhazza; Jens R. Nyengaard; Saleh Alwasel (Cell and Tissue Research, 2014)

Interrelationships between sirtuin 1 and transcription factors p53 and NF-κB (p50/p65) in the control of ovarian cell apoptosis and proliferation - Alexander V. Sirotkin; Petra Dekanová; Abdel Halim Harrath; Saleh Hamad Alwasel; Dušan Vašíček (Cell and Tissue Research, 2014)

Experimental Study of Bacterial Penetration into Chalk Rock: Mechanisms and Effect on Permeability - Amalia Halim; Alexander Shapiro; Anna Eliasson Lantz; Sidsel Marie Nielsen (Transport in Porous Media, 2014)